A corpus-based study of writer identity in qualitative and quantitative research articles - Dobakhti, Leila; Norizah Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Academic communication is now widely seen as a social activity where writers interact with their audience. Various studies have shown that authorial presence is one of the key strategies for achieving this interaction. This corpus-based study examines the degree of authorial presence through the use of first person pronouns (I, we, my, our, me, us) in 150 qualitative and 150 quantitative research articles in Applied Linguistics using the concordance freeware AntcConc.3.4.1w (Anthony 2014). The analysis shows a greater use of self-mention by qualitative research writers compared with their quantitative counterparts, suggesting that research design determines the degree of personal involvement in academic communication within the same discipline. It also suggests that while quantitative research is considered “objective” in nature, the writers still position themselves in their writing and try to interact with their audience. Qualitative analysis of discourse functions of subject pronouns showed great similarity between the two sub-corpora (qualitative and quantitative), stating results/claims and elaborating arguments as being the most frequent functions.